The influence of self-compassion on mental health of postgraduates: Mediating role of help-seeking behavior - Min, Lin; Jianchao, Ni; Mengyuan, Lin (Frontiers in Psychology, 2022)
This paper explores the relationship between self-compassion and mental health of postgraduates and the mediating role of help-seeking behavior based on the perspective of the dual-factor model (DFM) of mental health. 605 postgraduates were investigated by questionnaire survey method. The results showed that the DFM of mental health was better than the one-factor model for the mental health status of postgraduates. Among them, those with completely mental health accounted for the highest proportion (63.3%), followed by vulnerable (25.1%), troubled (9.1%), and symptomatic but content (2.5%). Self-compassion and non-professional help-seeking behavior had a positive predictive effect on the positive mental health factors of postgraduates, while self-compassion had a negative predictive effect on the psychological symptoms of postgraduates. Non-professional help-seeking behavior played a partial mediating role between self-compassion and positive mental health factors.